Safety and efficacy of tranexamic acid in minimizing perioperative bleeding in extrahepatic abdominal surgery: meta-analysis. Issue 2 (11th April 2021) - Koh, A; Adiamah, A; Gomez, D; Sanyal, S
Abstract: Background: Perioperative bleeding is associated with increased morbidity and mortality in patients undergoing elective abdominal surgery. The antifibrinolytic agent tranexamic acid (TXA) has been shown to reduce perioperative bleeding and mortality risk in patients with traumatic injuries, but there is a lack of evidence for its use in elective abdominal and pelvic surgery. This meta-analysis of RCTs evaluated the effectiveness and safety of TXA in elective extrahepatic abdominopelvic surgery. Methods: PubMed, Embase, and ClinicalTrial.gov databases were searched to identify relevant RCTs from January 1947 to May 2020. The primary outcome, intraoperative blood loss, and secondary outcomes, need for perioperative blood transfusion, units of blood transfused, thromboembolic events, and mortality, were extracted from included studies. Quantitative pooling of data was based on a random-effects model. Results: Some 19 studies reporting on 2205 patients who underwent abdominal, pelvic, gynaecological or urological surgery were included. TXA reduced intraoperative blood loss (mean difference –188.35 (95 per cent c.i. –254.98 to –121.72) ml) and the need for perioperative blood transfusion (odds ratio (OR) 0.43, 95 per cent c.i. 0.28 to 0.65). TXA had no impact on the incidence of thromboembolic events (OR 0.49, 0.18 to 1.35). No adverse drug reactions or in-hospital deaths were reported. Conclusion: TXA reduces intraoperative blood loss during elective extrahepatic abdominal and pelvic surgery without an increase in complications.